Pengawasan yang Efektif dalam Pengelolaan Peralatan Berat di Dinas Pekerjaan Umum Kota Medan - Diki Ariski; Tunggul Sihombing (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2023)
This study aims to find out and describe effective supervision in heavy equipment management in the Medan City Public Works Office. The research method used in this study is descriptive research with a qualitative approach. Data collection was carried out by means of interviews, observations, and documentation, the data obtained were analyzed qualitatively with the supervisory theory approach proposed by Siagian. The results of the study show that supervision of heavy equipment management at the Medan City Public Works Office has been effective. This can be seen from the clear role and target of supervision from people who are authorized to supervise the management of heavy equipment. Supervisors have been able to detect problems and take precautions. The problem is that there is no Standard Operating Procedure (SOP) for heavy equipment management which causes supervisors not to carry out objective supervision but to carry out supervision subjectively, namely conducting supervision at will without a clear procedure flow regarding what parts will be supervised.